THE EFFECTS OF MOTIVATIONAL FACTORS ON PUBLIC SECTOR EMPLOYEE PERFORMANCE DURING THE COVID-19: A CASE STUDY IN INDONESIA - Kathin, Muhammad Fath (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Good work quality in an organization can be optimal if employees' performance supports it. It is necessary to have things that encourage employees to improve the quality of their performance, one of which is work motivation. The decline in employee performance is suspected by the decrease in the employee's motivation level. This study aims to critically analyze the motivational factors which affect employee perspectives on their performance at the government-managed Financial Education and Training Agency facility in Indonesia during the COVID-19 pandemic from 2020 - 2022. The research design used is quantitative research. The data were obtained by using a questionnaire distributed to the sample used as the object of research, employees of the Finance Education and Training Agency (FETA) of the Republic of Indonesia. The data were then processed and analyzed with the SPSS program. The analysis technique used is simple descriptive analysis and multiple regression analysis. At the same time, the parameters used are employee motivation and performance based on respondents' perceptions with sampling techniques carried out in random sampling. Based on the analysis results, both partially and simultaneously, intrinsic and extrinsic motivation are significantly and positively related to employee performance during the pandemic.